2008
DOI: 10.1007/s00439-008-0585-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel hypomorphic MECP2 point mutation is associated with a neuropsychiatric phenotype

Abstract: The MECP2 gene on Xq28 encodes a transcriptional repressor, which binds to and modulates expression of active genes. Mutations in MECP2 cause classic or preserved speech variant Rett syndrome and intellectual disability in females and early demise or marked neurodevelopmental handicap in males. The consequences of a hypomorphic Mecp2 allele were recently investigated in a mouse model, which developed obesity, motor, social, learning, and behavioral deficits, predicting a human neurobehavioral syndrome. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…previously reported severely affected heterochromatin clustering in proline substitutions P101R, P101H and P152R. Similarly, Adegbola et al 18. reported disrupted MeCP2-heterochromatin binding for P152A, P152R and T158M.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…previously reported severely affected heterochromatin clustering in proline substitutions P101R, P101H and P152R. Similarly, Adegbola et al 18. reported disrupted MeCP2-heterochromatin binding for P152A, P152R and T158M.…”
Section: Discussionmentioning
confidence: 70%
“…P152R has been reported as a pathogenic variant only in females, showing classical, typical, and atypical Rett symptoms. In a single study, P152A was reported as a hypomorphic mutation in a male patient18. R106, R111, N126, R133, A140, P152, F157, T158 and R167 are conserved across all vertebrates (Fig.…”
mentioning
confidence: 99%
“…However, most of these mouse models have altered MeCP2 in all or most of the CNS, making it difficult to delineate the specific role of MeCP2 in different neurons. Overweight or obesity is a common phenotype in mouse models with deletion of MeCP2 in postmitotic neurons, in postnatal CNS and in Sim1-expressing neurons [22,25,26], as well as in some patients with atypical RTT [37][38][39][40]. A plausible mechanism for the overweight or obesity phenotype may be the reduced levels of brain-derived neuropeptide (BDNF), an established regulator of energy balance [41] and target of MeCP2 regulation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in the rare cases of familial transmission, mothers with favorably skewed XCI patterns can transmit a mutant allele to viable hemizygous male offspring, but these males typically die in infancy if they inherit total loss-of-function alleles (13,19). Males with more mild mutations survive, exhibiting varying degrees of intellectual disability and, frequently, neuropsychiatric symptoms, such as bipolar disorder (20), schizophrenia (21), and attention deficit/hyperactivity disorder (ADHD) (22,23). Importantly, these male patients helped broaden the phenotypic spectrum due to MECP2 mutations.…”
Section: Manifestations Of Diseasementioning
confidence: 99%